Characterization of micro-RNA in women with different ovarian reserve - Masood Abu-Halima (Nature Portfolio, 2021)
Abstract Women undergoing infertility treatment are routinely subjected to one or more tests of ovarian reserve. Therefore, an adequate assessment of the ovarian reserve is necessary for the treatment. In this study, we aimed to characterize the potential role of microRNAs (miRNAs) as biomarkers for women with different ovarian reserves. A total of 159 women were recruited in the study and classified according to their anti-Müllerian hormone (AMH) level into three groups: (1) low ovarian reserve (LAMH, n = 39), (2) normal ovarian reserve (NAMH, n = 80), and (3) high ovarian reserve (HAMH, n = 40). SurePrint Human miRNA array screening and reverse transcription-quantitative PCR (RT-qPCR) were respectively employed to screen and validate the miRNA abundance level in the three tested groups. Compared with NAMH, the abundance level of 34 and 98 miRNAs was found to be significantly altered in LAMH and HAMH, respectively. The abundance level of miRNAs was further validated by RT-qPCR in both, the screening samples as well as in an independent set of validation samples. The abundance levels of the validated miRNAs were significantly correlated with the AMH level. The best AUC value for the prediction of the increase and decrease in the AMH level was obtained for the miR-100-5p and miR-21-5p, respectively. The level of miRNAs abundance correlates with the level of AMH, which may serve as a tool for identifying women with a different ovarian reserve and may help to lay the ground for the development of novel diagnostic approaches.